PERANCANGAN SISTEM PELAYANAN ANTRIAN PASIEN PADA PRAKTEK DOKTER UMUM MENGGUNAKAN METODE FIFO (FIRST IN, FIRST OUT) BERBASIS WEBSITE - Claudia Afaf Azzahrah; Anita Andriani; Chamdan Mashuri; Indana Lazulfa (Inovate, 2025)
Along with the development of information technology, various aspects of life have undergone significant changes, including in the field of healthcare. Healthcare services are crucial in society, yet they face challenges in patient queue management. Long and disorganized queues can cause discomfort and dissatisfaction among patients, as well as disrupt the workflow of medical staff. At the general practice of Dr. Pudji Umbaran, M.Kp in Peterongan District, Jombang Regency, queue management often encounters issues due to a manual and inefficient registration system. This study aims to design and implement a patient queue system based on a website using the First In, First Out (FIFO) method to enhance time efficiency and service fairness. This method prioritizes patients based on their Arrival time, significantly reducing Waiting times and improving patient satisfaction. The research findings demonstrate that implementing the FIFO method effectively manages patient queues at the general practice, resulting in a significant decrease in waiting and processing times. This system offers an efficient solution to enhance service quality and operational efficiency in the doctor's practice. Keywords: Queue, FIFO, Practice, Service.